Determining Size Thresholds for High-Rise Net Zero Energy Office Buildings in Hot and Arid Climates: A Study of High-Rise Office Buildings in Dubai - HERNANDEZ, KATRINA ELISE AFRICA (2025)
This study investigates the feasibility and size thresholds of achieving Net Zero Energy Building (NZEB) performance in high-rise office buildings within the hot and arid climate of Dubai. As urban centres in the UAE pursue aggressive sustainability targets under the Net Zero 2050 strategy, the ability of large-scale buildings to meet NZEB criteria remains a critical yet underexplored area. The research aims to determine the specific building size—particularly in terms of height and floor area—beyond which achieving net-zero operational energy becomes impractical due to spatial and technical limitations. A simulation-based methodology, employing tools such as DesignBuilder and EnergyPlus, models various design interventions, passive and active energy strategies, and rooftop photovoltaic (PV) configurations to evaluate energy use intensity (EUI) across different building scales. Key findings reveal that while envelope optimisation and passive cooling significantly reduce energy demand, rooftop PV systems alone cannot fully offset energy loads in buildings beyond (around) 8-9 floors, primarily due to limited solar collection area relative to high cooling demands. The study identifies a practical threshold beyond which true NZEB status is unlikely without off-site renewables or major technological advancements. These insights inform design and policy frameworks aimed at reconciling ambitious energy goals with the realities of vertical urban development. The study concludes with recommendations for regulatory benchmarks and integrated design practices tailored to Dubai’s environmental context, offering a scalable blueprint for sustainable high-rise development in similar climatic regions.